The comparison of physical fitness component between adolescence tennis's players vs badminton's players / Nur Hazimah Ahmad Bakri - Ahmad Bakri, Nur Hazimah (Faculty of Sports Science and Recreation, 2018)
Tennis and badminton were both racquet sports. The purpose of this study was to examine the comparison of physical fitness component between adolescence tennis's players versus badminton's players. Forty adolescences male athletes Kelantan state level aged 13 to 18 years old; body weight 54.52kg ± 11.26kg; body height 1.62m ± O.08m were participate in this study. Physical fitness was carried out on twenty male tennis's players and twenty male badminton's players. The component of physical fitness test consisted of aerobic cardiovascular, agility, muscular strength, and flexibility. Independent sample T-test was used to analyze the mean differences of physical fitness component in both sports. Significant differences was reported for muscular strength fitness (p<O.05), while there were no differences recorded for aerobic cardiovascular, agility, muscular strength and flexibility. Tennis's players had higher muscular strength compared to badminton's players.